UTILIZATION Of Sn-Sb-S AS A NEW MATERIAL SENSITIZED SOLAR CELLS - Samosir, Harrys; Robiandi, Fadli; Shoodiqin, Dian Mart (Jurusan Teknik Mesin Fakultas Teknik Universitas Jember, 2024)
In this research process to observe the utilization of Sn-Sb-S for new material solar cells. With the SILAR (successive ionic layer adsorption and reaction) method, it was found that good conditions for growing quantum dots on the surface of TiO2 were 8 turns to get Sn-S and 6 turns for SbS and heated at 325 0C for 12 minutes. As for tools to analyze Sn-Sb-S there are quantum dots by observing using XRD and the size of quantum dots. UV Visible is used to observe the gap energy of 1.63 eV which includes a wavelength of 300-850 nm. The use of SEM to observe the morphological characteristics of Sn-Sb-S on the surface of TiO2 obtained the size of quantum dots 16.6 nm. The best sample with ZnSe passivation layer resulted in short circuit current density Jsc of 14.04 mA/cm2 open circuit voltage Voc of 0.46 V, fill factor FF of 39.91%, and power conversion efficiency Î· of 2.58% under 1 sun. Keywords: quantum dots, science materials, renewable energy